Hymenoptera fauna, with emphasis on Ichneumonidae from an area of Caatinga in Northeast Brazil - Fernandes, Daniell Rodrigo Rodrigues; Antunes, Nicanor Tiago Bueno; Araujo, Elton Lucio; Lara, Rogéria Inês Rosa; Perioto, Nelson Wanderley (EntomoBrasilis, 2020)
The objectives of this study were to carry out a survey of families of Hymenoptera, with emphasis on Ichneumonidae, in an area of Caatinga, and register the occurrence of new species, if any, for the biome. Samples were taken with Malaise traps between September and November 2008 in a native area of vegetation of Serra do Lima, municipality of Patu, Rio Grande do Norte, Brazil. 7,562 hymenopterans, from 11 superfamilies and 31 families, were collected. The most abundant superfamilies were: Chalcidoidea (2,887 specimens / 38.33% of the total), Platygastroidea (1,572 / 20.87%) and Vespoidea (1,131 / 15.02%) which constituted more than 70% of the captured hymenopterans. A total of 160 specimens of Ichneumonidae from 17 subfamilies were sampled, of which four are new records for Rio Grande do Norte: (Lycorininae, Nesomesochorinae, Phygadeuontinae and Tryphoninae). Altogether, 26 genera were recognized, with 16 new records for the state. Cryptophion espinozai Gauld & Janzen (Campopleginae) and Labena marginata Szépligeti (Labeninae) were registered for the first time in Caatinga. The obtained data demonstrate a considerable diversity of the studied groups in this area and also affirms the necessity of additional studies to establish the richness of this fauna in a more extensive and conclusive way.